Potential Study and Institutional Model for Sustainable Shrimp Cultivation Management in The Banten Bay Area, Serang - Farkan, Mochammad; Sumandiarsa, I Ketut; Margono, Margono; Marlina, Erni; Sektiana, Sinar Pagi (Jurnal Kelautan dan Perikanan Terapan (JKPT), 2023)
Shrimp is a superior commodity that has very good economic prospects. The coastal pond area of Banten Bay has an area of 5,415 Ha and has quite large potential for developing shrimp cultivation. Shrimp cultivation management institutions make an important contribution to the management of shrimp cultivation pond areas with efficiency, effectiveness and sustainability. This research aims to analyze fisheries potential and design an institutional model for managing coastal areas for shrimp cultivation on the coast of Banten Bay, Serang. Research location in the Banten Bay Coastal aquaculture area, Banten Province. The research was carried out in November 2022 – March 2023. Data collection methods were carried out using surveys, laboratory tests, interviews and focus group discussions (FGD). The data analysis method uses Interpretative Structural Modeling (ISM) and data processing uses Excel. Testing the validity and reliability of the questionnaire material using SPSS version 25. The elements analyzed consist of program objectives, influential community sectors, program needs, main obstacles and program implementing institutions. The results of the research show that the water and soil quality of Banten Bay ponds is categorized as very suitable, suitable and not suitable for shrimp cultivation. Based on land suitability, the estimated potential for white shrimp production on the coast of Banten Bay in one cycle is 41,926.8 tons/cycle or 125,780.4 tons/year . The management model shows the provision of production infrastructure according to needs, competent and professional human resources, coordination and cooperation in balanced use of aquaculture land are key elements for realizing sustainable shrimp cultivation management. The conclusion is that to realize sustainable management of shrimp cultivation areas on the coast of Banten Bay, the institutions that play the most role are the area management authorities and multi-sector research institutions.